Cognitive Scaffolding and Faith-Based Digital Literacy: Integrating Advanced Organizer and YouTube in Islamic Moral Education - Rahmawati, Mutia; Mahdiyah, Mahdiyah; Nisa, Zahratun; Sabirin, Muhamad; Mof, Yahya (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study investigates the effectiveness of integrating the Advanced Organizer learning model with YouTube media to strengthen Islamic digital literacy and learning outcomes in Islamic Moral Education (Akidah Akhlak) at MIN 7 Tapin. Employing a quantitative quasi-experimental design with pretest–posttest control groups, the study involved 104 sixth-grade students. The experimental group received learning through the Advanced Organizer model supported by Islamic YouTube content, while the control group received conventional instruction. Data were collected using validated achievement tests, Islamic digital literacy questionnaires, and learning observation sheets. Data analysis included normality, homogeneity, independent t-test, and Cohen’s d effect size using SPSS 26.0. The results revealed a significant difference between the experimental and control groups (p < 0.05) with a high effect size (d = 0.84), indicating that the integration significantly improved students’ conceptual understanding and ability to utilize digital media based on Islamic ethics. This study contributes theoretically by operationalizing Islamic digital literacy as a cognitively scaffolded instructional framework rather than a mere ethical or technical construct. The findings extend meaningful learning theory into faith-based digital education contexts by demonstrating how moral cognition can be systematically shaped through pre-organized multimedia learning.